DAMPAK PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP PEMBERIAN PUPUK ANORGANIK DAN KOMPOS LIMBAH LUMPUR IPAL PABRIK KARET DI PEMBIBITAN UTAMA - Maryani, Anis Tatik; Nurafifa, Nurafifa; Fathia, Nyimas Myrna Elsa; Rahmadani, Elfi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Jambi Province was one of the centers of oil palm plantations in Indonesia and there was another problem likes the age of the plants which had getting older and its worried caused decrease in production. Therefore, its was necessary to replanted oil palm for produced high quality seeds. The purpose of study was to determine the response of application and discover the best single dose of inorganic fertilizer and WWTP sludge compost in the growth of oil palm seedlings in the main nursery. This research was conducted at Teaching and Research Farm, UNJA (September-November 2022). This study used Completely Randomized Design with 5 treatments, (k0 = Urea, TSP, KCl recommended dose, k1 = Urea,TSP, KCl half recommended dose + 100 g WWTP sludge compost, k2 = Urea, TSP, KCl half recommended dose + 200 g WWTP sludge compost, k3 = Urea, TSP, KCl half recommended dose + 300 g WWTP sludge compost, k4 = Urea, TSP, KCl half recommended dose + 400 g WWTP sludge compost. The results showed the application of a single inorganic fertilizer and WWTP sludge compost was able to increased growth of seedling height, root dry weight and root volume. However, its has not been able to be increase of tuber diameter, the number of leaves, shoot dry weight and root crown ratio. Doses of Urea, TSP, KCl half recommended dose + 100 g WWTP sludge compost gived the best average growth of 6-month oil palm seedlings in the main nursery.